An Islamic Legal Analysis of Cryptocurrency Exchange into Fiat Money: A Qiyās-Based Study across the Four Madhhabs - Masithoh Masithoh; Rosiana Kholifah; Hanip Hidayatulloh (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the exchange of cryptocurrency for fiat money through the application of qiyas (analogical reasoning) within the perspectives of the four Islamic schools of jurisprudence, focusing on cryptocurrency's compliance with Sharia economic principles. Theoretical framework: The theoretical framework centers on Islamic legal concepts, specifically the principles of justice, honesty, and the prohibition of riba (usury), gharar (excessive uncertainty), and maisir (gambling). It examines how cryptocurrency aligns with these principles across the four major Islamic jurisprudential schools. Literature review: The literature review explores classical and contemporary scholarly works on qiyas methodologies and their application to digital currency transactions. It covers both Islamic jurisprudence regarding money and modern discussions on cryptocurrency's role in global finance and economics. Methods: A descriptive qualitative methodology with a literature review approach is employed to analyze the academic debates surrounding cryptocurrency. The study examines various scholarly sources discussing the application of qiyas to cryptocurrency transactions. Results: The study concludes that cryptocurrency is impermissible (haram) in Islamic law due to its failure to meet the essential characteristics of money as defined within the four Islamic jurisprudential schools. It also highlights how cryptocurrency contradicts key Sharia economic principles. Implications: The findings provide insight into the broader discourse on the permissibility of cryptocurrency in Islamic finance and offer a basis for future research and discussions on the integration of digital currencies within Sharia-compliant financial systems. Novelty: This study contributes to the academic debate by applying qiyas to the analysis of cryptocurrency, an emerging area within Islamic finance, and provides a clear verdict on its non-compliance with Sharia law.